A behavioral model of service-derived manufacturing in e-commerce companies from the innovation chain perspective: A case study from China - Yang Li; P.J. Kumarasinghe (Heliyon, 2023)
In recent years, the business landscape has been reshaped by the fusion of manufacturing and service industries, driven by the “Internet+'' initiative and the integration efforts of the Chinese government. This research focuses on the behavior model of service-derived manufacturing within e-commerce enterprises, specifically emphasizing a well-known Chinese enterprise. The study used a case study approach to analyze the manufacturing transformation process. It also reveals insights into the “reverse penetration” model e-commerce service firms adopt. This study aims to help industry practitioners, policymakers, and researchers understand how digital transformation and innovation can enhance manufacturing excellence within e-commerce enterprises. One key aspect examined is the role of e-commerce platforms in connecting manufacturers with consumers, optimizing production through big data analysis, reducing costs, and improving service integration.